2019
DOI: 10.33594/000000081
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Immunological Effects of CD73 Deficiency

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Recent studies have identified adenosine, a purine nucleoside, as a novel effector molecule of MDSCs. Extracellular ATP or ADP is hydrolyzed by CD39 (nucleoside triphosphate diphosphohydrolase) into AMP, which is in turn cleaved by CD73 (ecto-5'-nucleotidase) into adenosine (27). Both CD39 and CD73 are expressed by MDSCs from tumor-bearing mice and cancer patients, suggesting that MDSCs are capable of producing adenosine (28)(29)(30).…”
Section: Adenosine and Adenosine Receptorsmentioning
confidence: 99%
“…Recent studies have identified adenosine, a purine nucleoside, as a novel effector molecule of MDSCs. Extracellular ATP or ADP is hydrolyzed by CD39 (nucleoside triphosphate diphosphohydrolase) into AMP, which is in turn cleaved by CD73 (ecto-5'-nucleotidase) into adenosine (27). Both CD39 and CD73 are expressed by MDSCs from tumor-bearing mice and cancer patients, suggesting that MDSCs are capable of producing adenosine (28)(29)(30).…”
Section: Adenosine and Adenosine Receptorsmentioning
confidence: 99%